(untitled) (Research, Society and Development, 2020)
The work aimed to assess the fundamental and indispensable importance of environmental law in sustainable development through the preservation of the environment. Existing works were also used for indirect documentation through bibliographic review. It has an exploratory and qualitative character. Existing legislation in Brazil and in the world was presented and the effort that has been made by some countries to control the negative environmental impacts caused by the rampant growth of attacks on the environment. The relations between sustainable development, environmental law and preservation of the environment were also presented. Finally, the work was able to confirm that through environmental legislation, environmental law is able to provide sustainable development by preserving the environment. Only in this way does everyone tend to win.